ANALISIS FATWA MUI TENTANG PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL - Marasabessy, Fachrul (STAI Asy-Syukriyyah, 2023)
Copyright is a type of intellectual property right, which has been widely discussed by the public lately. Based on data from the International Data Corporation (IDC), Indonesia in 2007 was listed in the top five countries with the highest levels of piracy and the biggest violators of Intellectual Property Rights. Indonesia is also known as one of the